Bringing Interprofessional Case-Based Learning into the Classroom for Occupational Therapy and Speech-Language Pathology Students. Issue 1 (2nd January 2018) - Wallace, Sarah E.; Benson, Jeryl D.
ABSTRACT: Instructors are increasingly integrating interprofessional education (IPE) activities into academic programs to address curricular demands. IPE aims to increase the quality of collaborative services provided to patients. This article describes a case-based IPE activity designed for occupational therapy and speech-language pathology graduate students. This activity was designed as a small-scale integration of IPE to compliment large scale, multi-discipline learning activities. Students from two courses participated in an IPE activity that included one online and one in-class activity. The purpose of the activity was for students to gain knowledge of their respective roles in augmentative and alternative communication services. Students perceived increased knowledge and skills following this activity. Despite the somewhat small scale of this educational intervention, the instructors viewed the activity a valuable addition to their courses.